2020
DOI: 10.1088/1741-4326/ab6481
|View full text |Cite
|
Sign up to set email alerts
|

Full-wave model for the lower hybrid wave electric field vector with synthetic turbulence on Alcator C-Mod

Abstract: The effects of synthetic turbulence on lower hybrid (LH) wave field magnitude and polarization are studied on Alcator C-Mod. Three synthetic turbulence models are evaluated to assess the impact of filaments, holes, and periodic fluctuations on the LH wave electric fields. For all three cases, the synthetic turbulence can greatly impact the LH wave magnitude and polarization. Back scattering, interference and edge/SOL absorption of the LH wave is observed. This impact is shown to depend on the wavelength and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…To bypass this problem, the LH power spectrum at the separatrix must be measured, which is known to be a very difficult task. Recent attempts have been carried out recently to reach this goal [23,24]. Finally, it is clearly shown that the PAM LH antenna in HL-2A has a large potential to drive higher plasma current, with an improved efficiency.…”
Section: Hl-2a Tokamak Discharge #35261mentioning
confidence: 99%
See 1 more Smart Citation
“…To bypass this problem, the LH power spectrum at the separatrix must be measured, which is known to be a very difficult task. Recent attempts have been carried out recently to reach this goal [23,24]. Finally, it is clearly shown that the PAM LH antenna in HL-2A has a large potential to drive higher plasma current, with an improved efficiency.…”
Section: Hl-2a Tokamak Discharge #35261mentioning
confidence: 99%
“…Consequently, N k is not evolving at the scale of the perturbation, being a constant of the ray motion. Recently, several experimental investigations of the spectral characteristics of the LH wave near the separatrix have been carried out [23,24]. They will give certainly valuable details on the LH wave characteristics before entering the core plasma and contribute to improve the understanding of the overall LH wave dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This results in an increased angle-broadening effect compared to previous models, which in turn leads to relatively better match with experimental current drive measurement and reduced sensitively to simulation parameters. Another recent study using full-wave simulations predict large parasitic loss of LH power in the presence of SOL filaments [22]. This is attributed to significant partial-reflection and side-scattering.…”
Section: Introductionmentioning
confidence: 98%
“…Another recent study using full-wave simulations predict a large parasitic loss of LH power in the presence of SOL filaments (Lau et al. 2020). This is attributed to significant partial reflection and side scattering.…”
Section: Introductionmentioning
confidence: 99%